Masculinization of (Rhamdia quelen) through dietary administration of 17α-methyltestosterone - Weiss, Luciano A.; Bernardes Júnior, Jurandir J.; Machado, Claudia; de Oliveira Nuñer, Alex P. (Revista Colombiana de Ciencias Pecuarias, 2018)
Background: Production of monosex cultures of females is desirable in commercial aquaculture of certain species due to their higher growth rate. Ideally, females should be free of exogenous hormones. The initial step to produce hormone-free all-female offspring is masculinization of normal females to create sex reversed animals, called neomales, which are then be bred with normal females obtaining all-female offspring. Objective: To masculinize Rhamdia quelen fry by adding 17α-methyltestosterone (MT) hormone to the feed. Methods: Larvae of R. quelen were fed diets supplemented with 60, 80, or 100 mg MT/kg feed for 21 days. A control group was fed the same diet free of MT. At 150 days post-hatching, 30 fish of each treatment group were euthanized to evaluate gonadal changes using histological techniques. Results: MT significantly affected the differentiation of female gonads in the 60 and 80 mg MT/kg feed groups. Sex reversal was observed in all MT treatment groups, with 50, 40, and 20% neomales produced with 60, 80, and 100 mg MT/kg feed, respectively. Intersex gonads were observed only in the masculinization treatment groups. Inhibitory effects on gonadal development of females and males were observed at the highest MT doses. Conclusion: Dietary administration of MT effectively masculinizes R. quelen fry; however, the lowest dose of 60 mg/kg feed is recommended, since higher doses have inhibitory effects on gonadal development in both sexes.